Security Problems and Policies in the Post-Cold War Caribbean
XV, 249 p.
Keywords: This volume brings together contributions by eleven noted specialists on peace and security issues in the Caribbean. All chapters are based on recent research on the radically transformed regional situation in the post Cold-War context. Particular emphasis is placed on the formulation of security policies by the most relevant security actors, including both external powers present in the region, independent states and subregional groupings. This discussion is placed in the framework of post Cold-War security outlooks which focus on 'non-traditional' threats, mainly drugs and illegal migration.